Effects of nematode infection and mulching on the yield of plantain (Musa spp., AABgroup) ratoon crops and plantation longevity in Southeastern Nigeria - Coyne, Danny L.; Rotimi, O.; Speijer, P.; Schutter, B. de; Dubois, T.; Auwerkerken, A.; Tenkouano, A.; Waele, D. de (Brill, 2005)
The effects of nematode infection and mulching on plantain cv. Agbagba (Musa spp., AAB-group, false horn) yield and plantation longevity were examined in a field experiment at the High Rainfall Station of the International Institute of Tropical Agriculture (IITA) at Onne in southeastern Nigeria. The 2nd, 3rd and 4th crop cycles (1st, 2nd and 3rd ratoon, respectively) following the plant crop cycle (mother crop) were examined in nematode inoculated or non-inoculated and mulched or non-mulched treatments. Nematodes (Radopholus similis, Helicotylenchus multicinctus and, to a lesser extent, Helicotylenchus dihystera, Hoplolaimus pararobustus and Meloidogyne spp.) were inoculated at planting of the mother plant, but were also present in relatively high population densities in the non-inoculated treatments at harvest of the 1st crop cycle. Plants inoculated with nematodes failed to reach harvest and neither did plants in the non-inoculated non-mulched treatments in any ratoon. Only non-inoculated mulched plants reached harvest, producing 0.85, 1.22 and 0.2 Mg ha−1, respectively in the 1st, 2nd and 3rd ratoon, taking toppled, broken and dead plants into consideration. Mulched plants were larger, had more suckers, survived longer and had healthier root systems compared with non-mulched plants. Damage to roots was greater in the inoculated plants compared with the non-inoculated plants for the 1st and 2nd ratoons but not for the 3rd ratoon. Radopholus similis was most strongly associated with root damage (percentage root necrosis and dead roots), although H. multicinctus population densities were also positively correlated with percentage root necrosis. At flowering of the 1st ratoon, 71% of the inoculated non-mulched plants were dead compared with only 1% of the non-inoculated mulched plants. Helicotylenchus multicinctus remained the most abundant nematode throughout the experiment. Together with R. similis, it comprised over 95% of the plant-parasitic nematode population.